The Effect of Profitability and Exchange Rates on Stock Prices, with Earnings Per Share as an Intervening Variable, at Islamic Banks in Indonesia - Lia Siti Maziddah; Henny Medyawati (Eduvest - Journal of Universal Studies, 2026)
Stock prices are among the main indicators used to assess the performance of Islamic banks. However, stock prices of Islamic banks continue to exhibit volatility despite the sustainable growth of the Islamic banking industry in Indonesia. This condition indicates the potential influence of internal and external factors that may affect stock price movements. This study aimed to analyze the effects of profitability and exchange rates on stock prices, with earnings per share (EPS) as an intervening variable, in Islamic banks listed on the Indonesia Stock Exchange during the 2018–2024 period. Profitability was measured using return on assets (ROA) and return on equity (ROE). This study employed a quantitative approach with a purposive sampling method based on two criteria: Islamic banks that had been continuously listed on the Indonesia Stock Exchange from the second quarter of 2018 to the fourth quarter of 2024 and those that had consistently published financial reports throughout the research period. The data used were secondary data obtained from Yahoo Finance, financial reports available on the official websites of each bank, and the Bank Indonesia (BI) website. The data were analyzed using multiple linear regression analysis and the Sobel test. The results indicated that ROE had a significant effect on EPS, whereas ROA and exchange rates had no significant effect on EPS. EPS had a significant effect on stock prices, while ROA, ROE, and exchange rates had no significant direct effects on stock prices.